MICELLIZATION OF CASEIN-DEXSTRAN STRUCTURES OBTAINED IN THE MAILLARD REACTION - Roman Budkevich; Anastasiya Eremina; Elena Budkevich; Gennady Slyusarev (Вестник Северо-Кавказского федерального университета, 2022)
Micelles were prepared by the crosslinking copolymerization of casein and dextran in the Maillard reaction. Glycated proteins were identified using ft-IR spectrometry. Solutions of micelles are characterized by changing of optical properties. Micellization is reversible depending on pH. Micelles size ranges from 400 to 2000 nm when pH 4.6 and micelles dissociate at pH 7.0. Micelles can be used to encapsulate hydrophobic substances in the food industry.